Lev 19 - Warnung vor irreparabler Unreinheit durch das Zusammenbringen unvereinbarer Dinge und Handlungen - Wagner, Volker (Biblische Notizen, 2005)
With the exception of two cases only, the commandments and prohibitions compiled in Lev 19 can be understood as cautioning against the combination of incompatible things and acts. In accordance with 19,8b and numerous parallels to other collections of rules in the Old Testament, such combination leads to irreparable impurity and is to be punished by excommunication, death or banishment.